Balzac's lives - Brooks, Peter (New York Review Books, 2020)
"Peter Brooks's Balzac's Lives is a biography like no other, a vivid and searching portrait of the great novelist that is based on a close examination of the extraordinary characters that throng his work. More than anyone, Balzac invented the nineteenth-century novel, with its interwoven plots and diverse and overlapping realities-political, economic, domestic, psychological. Indeed, Oscar Wilde went so far as to say that Balzac invented the nineteenth century! It was, above all, the wonderful, unforgettable, extravagant characters he dreamed up and made flesh-entrepreneurs, bankers, inventors, industrialists, poets, artists, bohemians of both sexes, journalists, aristocrats, politicians, prostitutes-that allowed Balzac to bring to life the dynamic forces of the new era that ushered in our own. Brooks singles out the capitalist Gobseck, the aspiring writer Lucien de Rubempré, the ambitious politician Rastignac, and the gay criminal mastermind Collin, among others, to disclose the secret workings of a great writer's inner world"--
Keywords: Balzac, Honoré de, : 1799-1850 : Characters; Balzac, Honoré de, : 1799-1850 : Criticism and interpretation